Importance–performance analysis as a strategic tool for tourism marketers: The case of Taiwan's Destination Image. (January 2019) - Jeng, Chi-Ruey; Snyder, Adam T; Chen, Ching-Fu
Today's travelers, facilitated by increased leisure time, rising levels of disposable income and more efficient transportation networks, have the means to choose from among this much larger variety of destinations. As a result, tourism marketers are now faced with influencing consumer decision-making in an increasingly complex and competitive global marketplace. The purpose of this study is to engage discussion of different perceptions of travel to Taiwan particularly as a travel destination. It also will try to understand tourist's grievances and shortcomings of Taiwan as a travel destination and attempt to offer suggestions on improving these things. This study investigated international perceptions of Taiwan as a tourist destination and examined holistic attributes of a destination according to positive and negative contexts to determine the relation between travel customer satisfaction and travel attribute importance and performance. We also researched the level of difference in the perceived travel attributes of importance and performance as an indicator of service quality strengths and weaknesses. Our study results reveal the overall image of Taiwan to be a fun, free, hospitable place with friendly locals and an interesting culture. Climate, opportunity to increase knowledge, safety, political stability, relaxation, and scenery all scored as positive aspects of Taiwan. Free elicitation also corroborates this with the top four physiological attributes as friendly, fun, safe, and relaxing. Taiwan could use these attributes to its marketing advantage.